THE EFFECT OF SMOKING ON THE AUTONOMIC HEART REGULATION IN YOUNG "HEALTHY" MALE SMOKERS. - Zdravko Taralov; Peter Dimov; Kiril Terziyski; Ilcho Ilchev; Stefan Kostianev (Peytchinski Publishing, 2015)
The aim of our study was to compare the autonomic nervous system (ANS) activity between young "healthy" male smokers and non-smokers via the method of heart rate variability (HRV). Pulse oximetry, blood pressure, time and frequency domain and non-linear HRV parameters were measured in 21 healthy non-smoker males aged 28.0 ± 7.4 (mean±SD) and fourteen "healthy" smoker males aged 28.1±4.3 with 9.2±5.6 pack-years resting in supine position. Smokers were instructed to refrain from smoking at least 2 hours before the test. There was no difference between smokers and non-smoker, regarding oxygen saturation (96.3±1.6 vs 96.8±1.2% p=0.330) and blood pressure (117.4±9.4/75.5±7.1 vs 119.5±6.4/77.2±7.1 mmHg p=0.312) but smokers had higher heart rate at rest (76.3±14.2 vs 65.2±9.0 b/min p=0.008). Smokers had decreased standard deviation of normal-to-normal interval (SDNN) (40.3±16.3 vs 62.0±32.1 ms p=0.013) and root mean square of the successive differences (RMSSD) (24.9±12.5 vs 59.3±32.8 ms <0.001). Frequency domain analysis showed that smokers had decreased total power (lnTP) (7.0±0.8 vs 7.7±1.1 ms2 p=0.046), but higher LF/HF index (2.3±0.9 vs 1.4±0.8 p=0.004). Sample entropy was higher in non-smokers (1.4±0.3 vs 1.6±0.2 p=0.049). Cigarette smoking altered autonomic nervous function measured by HRV in young "healthy" males in the absence of subjective clinical signs or symptoms. The method may be applied in the clinical practice to detect early changes in the ANS activity.